2017
DOI: 10.1007/s00234-017-1796-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity of motor cortical network in patients with brachial plexus avulsion injury after contralateral cervical nerve transfer: a resting-state fMRI study

Abstract: IntroductionThe purpose of this study is to assess the functional connectivity of the motor cortical network in patients with brachial plexus avulsion injury (BPAI) after contralateral C7 nerve transfer, using resting-state functional magnetic resonance imaging (RS-fMRI).MethodsTwelve patients with total brachial plexus root avulsion underwent RS-fMRI after contralateral C7 nerve transfer. Seventeen healthy volunteers were also included in this fMRI study as controls. The hand motor seed regions were defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Furthermore, transhemispheric transposition of activated brain cortices is associated with the recovery of motor and sensory functions in ipsilesional upper limbs in patients with contralateral cervical 7 nerve transfer 21 . Resting-state MRI showed that interhemispheric functional connectivity of the primary motor cortex increased and the inter-hemispheric functional connectivity between the supplementary motor areas reduced bilaterally in patients with CTS 22 . However, these studies reveal brain function after treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, transhemispheric transposition of activated brain cortices is associated with the recovery of motor and sensory functions in ipsilesional upper limbs in patients with contralateral cervical 7 nerve transfer 21 . Resting-state MRI showed that interhemispheric functional connectivity of the primary motor cortex increased and the inter-hemispheric functional connectivity between the supplementary motor areas reduced bilaterally in patients with CTS 22 . However, these studies reveal brain function after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on brain function changes after other orthopedic surgeries have been performed 2022 . Changes in the brain following contralateral cervical 7 nerve transfer for brachial plexus injury have been reported 21,22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allodynia, elicited by a stimulus, is a noticeable feature in patients with neuropathic pain [31]. Neuropathic pain associated with BPA normally causes cold allodynia and mechanical allodynia (increased pain sensitivity) [32]. The pain states are generated and maintained by the activation of microglia and astrocytes in spinal cord, which usually lasts 3 months after BPA [33].…”
Section: Discussionmentioning
confidence: 99%
“…The success of nerve transfers is largely facilitated by cortical plasticity, which has been repeatedly demonstrated in the context of nerve transfer rehabilitation. 2,41,57, 73,86 Other factors known to influence success of nerve transfer are donor size matching with the recipient nerve and the robustness of preoperative electromyography-detected activity from the donor nerve/muscle. 69,70 For example, the optimal donor-to-nerve axon count ratio for elbow flexion seems to be > 0.7:1.…”
Section: Nerve Repair In the Modern Era: Nerve Transfersmentioning
confidence: 99%